PATRIOT: A phase I study to assess the tolerability, safety and biological effects of a specific ataxia telangiectasia and Rad3-related (ATR) inhibitor (AZD6738) as a single agent and in combination with palliative radiation therapy in patients with solid tumours. (August 2018) - Dillon, M.T.; Boylan, Z.; Smith, D.; Guevara, J.; Mohammed, K.; Peckitt, C.; Saunders, M.; Banerji, U.; Clack, G.; Smith, S.A.; Spicer, J.F.; Forster, M.D.; et al.
Highlights: Summary of a protocol for a phase I study combining the ATR inhibitor and palliative radiotherapy. Study design is discussed. Study aims and objectives, brief eligibility criteria, DLT criteria and dose escalation is discussed. Brief summary of translational research to be carried out. Abstract: PATRIOT is a phase I study of the ATR inhibitor, AZD6738, as monotherapy, and in combination with palliative radiotherapy. Here, we describe the protocol for this study, which opened in 2014 and is currently recruiting and comprises dose escalation of both drug and radiotherapy, and expansion cohorts.